Physico-Mechanical and Gas Permeability Characteristics of Kaolin Based Ceramic Membranes Prepared With a New Pore-Forming Agent - Obada, D.O.; Dodoo-Arhin, D.; Dauda, M.; Anafi, F.O.; Ahmed, A.S.; Ajayi, O.A. (Applied Clay Science, 2017)
The objective of this study was to prepare low-cost macroporous ceramic membranes using natural kaolin obtained from deposits in Nigeria and Ghana, and powdery high density polyethelene (PHDPE) as porogen agent. The ceramic membranes have been prepared with porogen content wt% between (0 and 20)% by die pressing. Pellets were fired at 1150 °C and soaking time of 4 h. The raw materials were characterized using TG/DTA, particle size distribution (PSD) and Zeta potential. The membranes cast as circular disks were subjected for characterization studies using XRD and SEM analysis. In a bid to correlate the physico-mechanical properties vis-à-vis pore former content, the effect of the sintering temperature and pore former (PHDPE) content on porosity, density, water absorption and mechanical strength were evaluated. The membrane corrosion resistance was found to be unaltered with experimental conditions. Obtained membranes showed good porosity with maximum at about 62% with a mechanical strength that does not exceed 18 MPa. These membranes can be considered as efficient regarding the results shown in the gas permeation tests at different sintering temperatures. A PHDPE percentage of 20% and a sintering temperature of 1150 °C were chosen as the optimum for gas permeation based on enlarged pore diameter of sintered membranes.
Keywords: Kaolin; PHDPE; Porosity; Sintering; Membrane; Permeability